Pengaruh Pengunaan Media Audio Visual Terhadap Ketepatan Hasil Shooting Permainan Futsal - Ruslandi, Lalan; Sumarsono, Rhama Nurwansyah; Gani, Ruslan Abdul (Jurnal Porkes, 2022)
Futsal is a sport that is popular with people in the current era because futsal is easy to play and there are not many rules like other sports. The purpose of this study was to examine whether there was an effect of training methods using audiovisual media on the accuracy of shooting results. The population in this study was 20 extracurricular students at SMA PGRI Cicurug. The sampling technique in this study used total sampling, which consisted of 20 futsal extracurricular students. The instrument used in this study was a shooting accuracy test, then extracurricular students were given the treatment of viewing videos 3 times a week for 8 meetings. Research data were analyzed using the normality test and t-test. testing the hypothesis of the calculation results obtained that the significance value of the experimental group's tcount was 5.037 > ttable 2.093 with a value of 0.000 <0.05, so the experimental group had a significant influence. When viewed from the pretest average of 10.9 and the posttest average of 12.95, a mean difference of 2.05 is obtained, this indicates that the audiovisual media on the accuracy of the shooting results gives a better change, namely 18.80% compared to before being given audiovisual media . Thus, this research has the effect of training using audiovisual media in the form of videos on the accuracy of futsal shooting results which are categorized as good.